THE ABDOMINAL DRAWING-IN MANEUVER AS WELL AS CORE STRENGTHENING EXERCISE IN IMPROVING THE POWER OF CORE MUSCLE ON SMAN 1 GIANYAR STUDENTS - Purwani, I Gusti Ayu Mega; Tianing, Ni Wayan; Griadhi, I Putu Adiartha (Majalah Ilmiah Fisioterapi Indonesia; Vol 5 No 3 (2017): Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT This study aims to determine the effect of abdominal drawing-in maneuver and core strengthening exercise in increasing the strength of the core muscles performed on female students SMAN 1 Gianyar. The research design used Randomize Pre and Post Test with Control Group Design with sampling technique using simple random sampling so that 30 samples were divided into 2 groups, the treatment group (abdominal drawing-in maneuver) and the control group (core strengthening exercise) 3 times a week for 4 weeks. There was a significant increase of core muscle strength in both groups with mean improvement in treatment group of 64,05 ± 23,6 (p <0,05) and control group was 69,91 ± 23,2 (p <0,05) . Based on paired sample t-test in the treatment group and control group, there was no significant result (p> 0,05) in both groups which means abdominal drawing-in maneuver practice as well as core strengthening exercise in increasing the strength of the core muscle. Keyword : Core Muscle, muscle strength, Abdominal Drawing -in Maneuver, Core Strengthening Exercise